HUBUNGAN PARITAS DAN PARTUS LAMA DENGAN KEJADIAN PERDARAHAN POST PARTUM DI RSUD KOTA PRABUMULIH - Precelia Fransiska (JURNAL SMART ANKES, 2022)
Post partum bleeding is bleeding that occurs after the delivery process with the amount of bleeding exceeding 500cc. The purpose of the study was to determine the relationship between parity and prolonged labor with the incidence of postpartum hemorrhage in the general hospital on prabumulih city. The research method was analytic, using a cross sectional approach. The population of this study were all mothers who gave birth in the general hospital on prabumulih city. The sampling in this study used a random sampling technique, namely 326 respondents. The research instrument is a checklist. The results of the study based on univariate analysis showed that from 326 respondents there were 122 respondents (37.4%) who experienced postpartum hemorrhage and 204 respondents (62.6%) who did not experience postpartum hemorrhage, there were 54 respondents (16.6%) who experienced postpartum hemorrhage. have high risk parity and 272 respondents (83.4%) who have low risk parity, there are 68 respondents (20.9%) who were diagnosed with prolonged labor and 258 respondents (79.1%) who were not diagnosed with prolonged labor. From the bivariate analysis, it was found that from 54 respondents who had high risk parity, 43 respondents (13.2%) were diagnosed with postpartum hemorrhage, from 68 respondents who were diagnosed with prolonged labor, 52 respondents (16%) were diagnosed with postpartum hemorrhage. The conclusion, there is a significant relationship between parity and postpartum hemorrhage with a P value of 0.000 < 0.05, there is a significant relationship between prolonged labor and postpartum hemorrhage with a P value of 0.000 < 0.05 Keywords: postpartum hemorrhage, parity, prolonged labor